2020
DOI: 10.36656/jpk2r.v2i2.223
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kepemimpinan Dengan Kinerja Kesehatan Di Rumah Sakit Umum Medan Tere Margareth

Abstract: Based on data from the Hospital Accreditation Commission, out of 2,379 private and state hospitals in Indonesia, only 1,032 hospitals (43.4%) are accredited. This can reflect the performance of health workers in hospitals is not optimal, because the performance of health workers is one of the determinants of organizational success in achieving hospital goals. The purpose of this study is to link leadership with the performance of health workers. This type of research is analytic with cross-sectional desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Performance appraisal is very important in supporting the success of Performance Management which is a goal-oriented process to ensure that organizational processes run optimally in the productivity of individual employees, teams, and the organization itself in order to achieve the main objectives of the organization by conducting performance appraisals (Mondy & Martocchio, 2016). From the results of previous research, it is found that there are several factors related to performance including work motivation, job satisfaction, work environment, leadership, and job design (Handayani et al, 2018;Khoir & Rosidah, 2016;Santari et al, 2022;Saputra & Dihan, 2020;Sitepu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Performance appraisal is very important in supporting the success of Performance Management which is a goal-oriented process to ensure that organizational processes run optimally in the productivity of individual employees, teams, and the organization itself in order to achieve the main objectives of the organization by conducting performance appraisals (Mondy & Martocchio, 2016). From the results of previous research, it is found that there are several factors related to performance including work motivation, job satisfaction, work environment, leadership, and job design (Handayani et al, 2018;Khoir & Rosidah, 2016;Santari et al, 2022;Saputra & Dihan, 2020;Sitepu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%